Role of insulin signaling dysregulation in pulmonary vascular remodeling in rats with monocrotaline-induced pulmonary arterial hypertension - Gao, Gufeng; Chen, Ai; Yan, Yan; Sagor, Mohammad Ismail Hajary; Lin, Weijun; Lin, Huakan; Lian, Guili; Xie, Liangdi; Luo, Li (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPulmonary arterial hypertension (PAH) is a severe disease marked by the remodeling of arteries due to the abnormal growth of vascular cells, including pulmonary arterial smooth muscle cells (PASMCs). The insulin receptor substrate-1 (IRS-1) plays a crucial role in the insulin signaling pathway; however, its function in PAH is still not fully understood. The objective of this research was to explore the role of the protein kinase C (PKC)/IRS-1/ERK signaling pathway in the progression of PAH and its influence on the proliferation and migration of PASMCs.MethodsTo establish the PAH model, low-dose Monocrotaline (MCT) was intraperitoneally administered to male SD rats twice a week. Four weeks following the initial treatment, measurements of mean pulmonary arterial pressure (mPAP) and the right ventricular hypertrophy index (RVHI) were conducted. Additionally, calculations were performed to determine the percentage of wall area (WA%) and wall thickness (WT%). The protein levels of PKC, p-PKC, IRS-1, p-IRS-1 (Ser318), ERK, and p-ERK in lung tissues were assessed. in vitro experiments involved stimulating PASMCs with platelet-derived growth factor-BB (PDGF-BB) to promote proliferation and migration. The impact of the PKC inhibitor Gö 6983 and IRS-1 overexpression via adenoviral vectors (AdIRS-1) on the PKC/IRS-1/ERK signaling pathway and PASMCs behavior was analyzed through Western blotting, EdU incorporation assay, and wound healing assay.ResultsIn PAH rats, there was a significant rise in mPAP and RVHI (p < 0.05), accompanied by notable pulmonary vascular remodeling. Analysis of lung tissues revealed enhanced levels of p-PKC, p-IRS-1(Ser318), and p-ERK, whereas the expression of total IRS-1 decreased significantly (p < 0.05). In PASMCs stimulated with PDGF-BB, a similar trend of increased p-PKC, p-IRS-1(Ser318), and p-ERK levels was observed, along with a decrease in IRS-1 expression. The administration of Gö 6983 or the overexpression of IRS-1 effectively inhibited the activation of the PKC/IRS-1/ERK signaling pathway, leading to reduced proliferation and migration of PASMCs compared to stimulation with PDGF-BB alone (p < 0.05).ConclusionsThe PKC/IRS-1/ERK signaling pathway is implicated in the abnormal proliferation and migration of PASMCs, contributing to pulmonary vascular remodeling in PAH. Targeting this pathway through PKC inhibition or IRS-1 stabilization may offer novel therapeutic strategies for PAH management.